Discussion on the correlation between active fault and geological disaster distribution in the Ganzi area, western Sichuan province, China - QIN Yulong; WU Jianliang; ZHAN Hanyu; XIONG Changli; JIA Chun; BAI Xianzhou; LI Mingze; WU Wenhui; XU Yunfeng (Dizhi lixue xuebao, 2021)
Geological disaster effect of active fault zone is a major research area in the field of engineering geology and geological disaster. Located in the west margin of the Qinghai-Tibet plateau, the Ganzi area in western Sichuan Province has underwent different geological events, which have created its unique topography, special landforms and geological phenomena. The intensive neotectonic movements in western Sichuan have caused frequent, various, and widely distributed geological disasters, threatening the safety of human life and property and damaging social life and economic development. In this study, we analyzed the correlation between active fault and spatial distribution of geological disaster sites, and summarized the rules between their spatial distributions. It is considered that active fault is one of the internal dynamic conditions causing geological disasters in the Ganzi area, and it is closely related to geological disasters in space. In average, around the main active fault, there is 0.1 site per km2 within the range of 0~1 km, 0.05 site per km2 within 1~2 km and 0.3 site per km2 within 2~5 km. Geological disaster monitoring and prevention is urgently needed along the active faults, so as to provide basis and suggestions for reducing or avoiding geological disasters.